Harnessing Trichoderma spp. for Sustainable Plant Disease Management: Mechanisms, Metabolites, and Application Strategies- A review - Ayyandurai M; M. Theradimani; R. Balakumbahan; I. Yesu Raja; A.Kavitha Pushpam; S.Merina Prem Kumari (Journal of Animal and Plant Sciences, 2024)
Abstract Trichoderma spp. has emerged as a potent biological control agent (BCA) for managing plant diseases, offering sustainable and eco-friendly alternatives to chemical fungicides. This review explores the multifaceted roles of Trichoderma spp. in plant disease suppression, growth promotion, and induced systemic resistance. The success of Trichoderma spp. as a BCA lies in its diverse mechanisms of action, including mycoparasitism, competition, antibiosis, and induction of systemic resistance. Notably, Trichoderma spp. produce a range of volatile compounds that inhibit plant pathogens while promoting plant growth. Furthermore, their ability to solubilize nutrients, such as iron and phosphate, and produce phytohormones like auxins, contributes to enhanced plant vitality. Molecular characterization has facilitated the identification of various Trichoderma species with distinct biocontrol properties. Application methods, including seed treatment, soil application, and foliar spray, have been developed to optimize the efficacy of Trichoderma-based biocontrol strategies. Overall, Trichoderma spp. showcases its potential as a versatile and effective BCA for integrated disease management and sustainable agriculture
Keywords: Trichoderma spp.; Biological control agent; Plant diseases; Disease suppression; Growth promotion; S